Fantastic plastic? Experimental evaluation of polyurethane bone substitutes as proxies for human bone in trauma simulations. Issue 5 (September 2015) - Smith, Martin J.; James, Stephen; Pover, Tim; Ball, Nina; Barnetson, Victoria; Foster, Bethany; Guy, Carl; Rickman, John; Walton, Virginia
Graphical abstract